Beyond Phylogenetics: Darwinian Evolution of Actin - Moret, Marcelo A.; Zebende, Gilney; Phillips, James C.; Toledo Marín, Javier Quetzalcóatl; García Naumis, Gerardo (Revista Mexicana de Ingenieria Biomedica, 2018)
Actin polymerizes to form cytoskeletons which stabilize and direct motion of cellular walls. It is one of the most stable proteins, having evolved little from algae and yeast, and very little from fish. Here we analyze actin evolu-tion using modern theories of water-protein shaping interactions, and how these have evolved to optimize protein functions. We conclude that the failure of phylogenetic analysis to identify positive Darwinian evolution has been caused by 20th century technical limitations. These are overcome using 21st century thermodynamic scaling and modular averaging. The results for actin are especially striking, and reflect dual stable structures, globular and polymerized.